(untitled) (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
MULTIDISCIPLINARY PERIODONTIA-ORTHODONTIA APPROACH IN A CASE OF MIDLINE DIASTEMA WITH LABIAL FRENECTOMY USING ELECTROSURGERY Media Sukmalia Adibah, Eka Pramudita Ramadhany, Valeo Adika Laksana, Ni Luh Desy Ayu Susilahati 1 - 6 RE-TREATMENT OF MISMANAGED BILATERAL CONDYLAR FRACTURE AND POST-SURGICAL COMPLICATION Oyagi Shuka, Nyoman Ayu Anggayanti, Anak Agung Manik Swayoga, Agus Dwi Sastrawan, Eka Marwansyah Oli’i 7 - 14 THE RELATIONSHIP OF ORAL HEALTH AND QUALITY OF LIFE FOR ELDERLY AT THE TRESNA WERDHA NIRWANA SOCIAL ORGANIZATION PURI SAMARINDA Alifia Auralia, Nuryanni Dihin Utami, Endang Sawitri, Elliana Martalina, Ronny Isnuwardana, Cicih Bhakti Purnamasari 15 - 21 EFFECT OF BROWN ALGAE (Sargassum Sp) GEL ON ALKALINE PHOSPHATASE LEVELS IN PERIODONTITIS RATS INDUCED BY SILK LIGATION MODEL Muhamat Muhtar S Abdurrohman, Faruq Abdurrohman Muhammad, Tahta Danifatis Sunnah, Ade Ismail A. K, Christina Mahardika 22 - 28 THE RELATIONSHIP OF KNOWLEDGE AND THE BEHAVIOR OF DENTAL POST GRADUATED STUDENTS REGARDING PERSONAL PROTECTIVE EQUIPMENT AT RSGM SARASWATI DENPASAR Dwiastutik Listiantari, Ni Luh Gede Aris Maytadewi Negara, Agnes Ayu Biomi 29 - 33 COMBINATION OF REGENERATIVE THERAPY AND FREE GINGIVAL GRAFT IN STAGE IV PERIODONTITIS: CASE REPORT Resky Ramadhani, Ayu Rahayu Feblina, Dian Setiawati 34 - 39 EFFECT OF KECEMCEM (Spondias pinnata) EXTRACT ON ANGIOGENESIS OF GINGIVA AFTER CURETASE OF WISTAR RATS Eka Pramudita Ramadhany, Media Sukmalia Adibah, I Ketut Suandika Dharma Yanta 40 - 45 EFFECT OF 4 wt% HYDROXYAPATITE PASTA ON DENTAL EMAIL HARDNESS James Hartono Santoso, Anastasia Elsa Prahasti, Elline 46 - 52 TEST OF RESISTANCE OF ALPUKAT (Persea americana mill) FRUIT EXTRACT ON THE GROWTH OF THE Streptococcus mutans Putu Rusmiany, Nyoman Nurdeviyanti, Ilma Yudistian, Agnesia Lorenza 53 - 59 DIFFERENCES IN FLOW RATE AND SALIVA PH IN USERS AND NON-USERS OF FIXED ORTHODONTIC APPLIANCES Viona Sekar Melati, Ernawati, Ageng Wicaksono 60 - 66 THE EFFECTIVENESS OF PLATELET RICH FIBRIN, CONNECTIVE TISSUE GRAFT AND THEIR COMBINATION IN THE CLOSURE OF GINGIVAL RECESSION: A SYSTEMATIC REVIEW Dian Anggraini, Irma Ervina, Aini Hariyani Nasution 67 - 75 QUANTITATIVE ANALYSIS OF THE COMPLETENESS OF GENERAL POLY OUTPATIENT MEDICAL RECORD DOCUMENTS AT COMMUNITY HEALTH CENTER I EAST DENPASAR Anak Agung Putri Adnyaswari, Putu Ika Farmani, Made Karma Maha Wirajaya 76 - 82 POTENTIAL OF VIRGIN COCONUT OIL PASTE AS EXTRINSIC DENTAL STAIN REMOVAL Khusnul Munika Listari, Siham 83 - 89 THE EFFECTIVENESS OF METRONIDAZOLE GELS IN THE MANAGEMENT OF PERIODONTAL DISEASE Citra Jasmin Cangara, Hasanuddin Thahir 90 - 95 THE BENEFICIAL EFFECTS OF PROPOLIS ON OSTEOBLAST DIFFERENTIATION: A LITERATURE REVIEW Jessy Wijaya, Rezmelia Sari, Suryono 96 - 102 INCIDENCE OF ORAL CANDIDIASIS IN FIXED ORTHODONTIC APPLIANCES Wahyuni Dyah Parmasari, Masfufatun, Tri Juliati 103 - 107 LASER-ASSISTED CROWN LENGTHENING: CLINICAL EFFICACY AND ADVANTAGES OVER CONVENTIONAL TECHNIQUES (SYSTEMATIC REVIEW) Rieska Rachmasari, Fatimah Maria Tadjoedin 108 - 117 REGENERATIVE PERIODONTAL TREATMENT AS MANAGEMENT OF CHRONIC PERIODONTITIS: A CASE REPORT Ainun Isnaeni Ilham, Daniel Tetan El, Sri Oktawati 118 - 123 CHITOSAN COLLAGEN HYDROGEL: A POTENTIAL SCAFFOLD BIOMATERIAL FOR PERIODONTAL REGENERATIVE TREATMENT Dharmmesti Anindita Wijayanti, Dahlia Herawati, Vincensia Maria Karina, Kwartarini Murdiastuti 124 - 132 EFFECTIVENESS OF SOCKET PRESERVATION IN MAINTAINING ALVEOLAR BONE VOLUME: A SYSTEMATIC REVIEW Fahrur Rozi Lubis, Irma Ervina, Martina Amalia 133 - 138 CONVOLUTIONAL NEURAL NETWORK (CNN) BASED ON ARTIFICIAL INTELLIGENCE IN PERIODONTAL DISEASES DIAGNOSIS Nurul Huda Danial, Dian Setiawati 139 - 148 FUNCTIONAL CROWN LENGTHENING AS A PRE-RESTORATIVE PROCEDURE IN THE AESTHETIC ZONE Vidya Nursolihati, Osa Amila Hafiyyah 149 - 155 MANAGEMENT OF BACTERIAL PLAQUE-INDUCED GINGIVAL ENLARGEMENT: CASE REPORT Martina Amalia, Cut Ati Ningsih, Widianto Meydhiono 156 - 163 EFFECT OF SOLVENT TYPE ON THE AMOUNT OF YIELD FROM MACERATION OF MORINGA PLANTS (Moringa oleifera) Wulan Anggestia, Sri Pandu Utami, Darmawangsa,Widya P. Sari, Difa Dirgantara 164 - 169 FIXED DOSE COMBINATION OF MECOBALAMIN AND PREGABALIN IN THE TREATMENT OF OROFACIAL NEUROPATHIC PAIN Manuel Dwiyanto Hardjo Lugito 170 - 175